Are Women Paid Less Because of Discrimination? Gender, Occupation and Parental Status - Tinna Rós Rudolfsdóttir 1990- (2019)
Verkefnið er lokað í fjögur ár með samþykki Viðskiptafræðideildar. Research has shown that the gender wage gap is still present in Iceland. However, the causal mechanisms for these wage discrepancies remain elusive. The main aim of the study was to examine the role of discrimination as a contributing factor to the unexplained gender wage gap. Using a survey experiment, it was examined whether the general public would offer or advise a woman about lower salaries than a man. Second, it was examined whether individuals would advise or offer a mother lower salaries than a childless woman and if that difference was greater than when a father or a childless man is involved. Finally, possible reasons for wage discrimination were examined, such as by perceived abilities or skills. A total of 974 Icelanders participated in the study, 481 men and 493 women (median age = 46-55 years). Participants were instructed to put themselves in the role of a human resource manager, where they received two job advertisements (sales representative and department manager) and evaluated two randomly assigned resumes across several measures. Results revealed no significant differences between what was offered to hired female or male applicants. However, female applicants were advised to ask for approximately 3-7% lower salaries than male applicants. Furthermore, results revealed that participants thought female applicants would settle for approximately 3-12% lower salaries than male applicants and that they would be offered approximately 4-16% lower salaries than male applicants. Differences in salary evaluations were more prominent for the department manager position. These differences were due to the evaluation of both female and male participants, and even more so, to the evaluation of female participants. In terms of parental status, no significant differences were found between salaries participants would offer or advise parents versus nonparents. When applicants’ perceived abilities and skills were examined, results revealed that ...